Four-dimensional lattices from ℚ(√2,√5) - Interlando, J. Carmelo; Neto, Trajano Pires da Nóbrega [UNESP]; Nunes, José Valter Lopes; Lopes, José Othon Dantas (Academic Publications, 2017)
Four-dimensional lattices with block circulant generator matrices are constructed from submodules of the ring of integers of the totally real number field ℚ(√2,√5). The obtained lattices are of full diversity and their sphere packing densities are the highest known for the given relative minimum product distances.
Keywords: Lattices; Minimum product distance; Modulation; Number fields; Sphere packings